2009
DOI: 10.1007/s10508-009-9565-8
|View full text |Cite
|
Sign up to set email alerts
|

Doing Gender in Sex and Sex Research

Abstract: Gender is central to sexuality, and vice versa, but there are a number of difficulties with the treatment of gender in sex research. Apparently, it is hard to find a balance between two conflicting needs. First, obviously, it is necessary to make distinctions between women and men, for political as well as research-technical and theoretical reasons. A second requirement, at odds with the first one, is the necessity to understand gender and its relation to sexuality and the body as much more complex than simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 95 publications
2
42
0
Order By: Relevance
“…I have argued that solitary and partnered sexualities are separable. I have highlighted the importance of gender/sex sexuality as one, but not the only or major feature of sexuality, incorporating gender/sex without focusing only on its relevance for difference (Bancroft, 2000b;Katz-Wise & Hyde, 2014;Unger, 1979;Vanwesenbeeck, 2009). And, I have disentangled gender and sex from each other and gender/sex itself when these are more typically conflated (e.g., Freud, 1905).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I have argued that solitary and partnered sexualities are separable. I have highlighted the importance of gender/sex sexuality as one, but not the only or major feature of sexuality, incorporating gender/sex without focusing only on its relevance for difference (Bancroft, 2000b;Katz-Wise & Hyde, 2014;Unger, 1979;Vanwesenbeeck, 2009). And, I have disentangled gender and sex from each other and gender/sex itself when these are more typically conflated (e.g., Freud, 1905).…”
Section: Discussionmentioning
confidence: 99%
“…Individual gender/sex and gender/sex sexuality are separate phenomena (e.g., Storms, 1980), though they can also be interconnected (Vanwesenbeeck, 2009). For example, gender (not sex) has predictive power for lifetime number of sexual partners such that femininity in women and men predicts fewer lifetime partners (Tate, 2011).…”
Section: Sexual Configurations Theorymentioning
confidence: 99%
“…However, more work is needed to increase our understanding of gender-related factors and processes that influence sexual behavior (Vanwesenbeeck 2009). Cross-culturally, men report more positive attitudes toward and willingness to engage in casual sex than women (Petersen and Hyde 2010;Schmitt 2005-participants sampled from 48 nations).…”
Section: Introductionmentioning
confidence: 99%
“…However a recent study of patients with RA showed that male gender was associated with a larger negative impact on sexual activity (Helland, Dagfinrud, and Kvien 2008), which indicates that this field needs further exploration. There are of course several other factors influencing sexual health and the perspective of gender on sexual health is complex (Vanwesenbeeck 2009), but most individuals with RA are women and the subject of sexual health needs to be discussed with a gender perspective since there are differences concerning how RA affects the sexual health of women and men. As examples, women often experience that feelings of intimacy are more important than sexual arousal (Basson and Schultz 2007), and women often have more joint pain during sexual activities (van Berlo et al 2007).…”
Section: Communication About Sexual Healthmentioning
confidence: 99%